Linear Algebra Solutions 9

Linear Algebra Solutions 9 - A + (3-3 n +1 ) 2 I 2 = (3 n...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
Section 2 . 4 2. Suppose B = a b c d e f and that AB = I 2 . Then - 1 0 1 0 1 0 a b c d e f = 1 0 0 1 = - a + e - b + f c + e d + f . Hence - a + e = 1 c + e = 0 , - b + f = 0 d + f = 1 ; e = a + 1 c = - e = - ( a + 1) , f = b d = 1 - f = 1 - b ; B = a b - a - 1 1 - b a + 1 b . Next, ( BA ) 2 B = ( BA )( BA ) B = B ( AB )( AB ) = BI 2 I 2 = BI 2 = B 4. Let p n denote the statement A n = (3 n - 1) 2 A + (3 - 3 n ) 2 I 2 . Then p 1 asserts that A = (3 - 1) 2 A + (3 - 3) 2 I 2 , which is true. So let n 1 and assume p n . Then from (1), A n +1 = A · A n = A n (3 n - 1) 2 A + (3 - 3 n ) 2 I 2 o = (3 n - 1) 2 A 2 + (3 - 3 n ) 2 A = (3 n - 1) 2 (4 A - 3 I 2 ) + (3 - 3 n ) 2 A = (3 n - 1)4+(3 - 3 n ) 2 A + (3 n - 1)( - 3) 2 I 2 = (4 · 3 n - 3 n ) - 1 2
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: A + (3-3 n +1 ) 2 I 2 = (3 n +1-1) 2 A + (3-3 n +1 ) 2 I 2 . Hence p n +1 is true and the induction proceeds. 5. The equation x n +1 = ax n + bx n-1 is seen to be equivalent to x n +1 x n = a b 1 x n x n-1 12...
View Full Document

This note was uploaded on 12/19/2011 for the course MAS 3105 taught by Professor Dreibelbis during the Fall '10 term at UNF.

Ask a homework question - tutors are online